Influence of Conditions of Cryogenic Molybdenite Grinding on the Activity of Bulk Sulfide Hydrotreating Catalysts - Mikubaeva E. V. Elena Victorovna; Akimov A. S. Akim Semenovich; Zhuravkov S. P. Sergey Petrovich; Sizova N. V. Nataljya Vitaljevna; Vosmerikov A. V. Aleksandr Vladimirovich; Prosvirin I. P. Igor Petrovich; Zaykovskiy V. I. Vladimir Ivanovich; Uymin M. A. Mikhail Aleksandrovich; Maykov V. V. Vladislav Vladimirovich; Lisovaya K. N. Kseniya Nikolaevna; Fedushchak T. A. Taisiya Aleksandrovna (2020, 2020)
Title screen